2018
DOI: 10.1002/chem.201805585
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis in Microdroplets of 2‐Phenyl‐2,3‐dihydrophthalazine‐1,4‐dione from Phenyl Hydrazine with Phthalic Anhydride or Phthalic Acid

Abstract: Pyridazine derivatives are privileged structures because of their potential biological and optical properties. Traditional synthetic methods usually require acid or base as a catalyst under reflux conditions with reaction times ranging from hours to a few days or require microwave assistance to induce the reaction. Herein, this work presents the accelerated synthesis of a pyridazine derivative, 2‐phenyl‐2,3‐dihydrophthalazine‐1,4‐dione (PDHP), in electrosprayed microdroplets containing an equimolar mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“… 1 It is also possible for the reaction products in microdroplets to differ substantially compared to those from the same reaction conditions in bulk solution. 2 Recent work has demonstrated that aqueous microdroplets can cause spontaneous reduction. Two examples are the formation of gold nanoparticles and nanowires from aqueous microdroplets containing only chloroauric acid, 3 and the reduction of a number of different organic compounds dissolved in aqueous microdroplets, such as the conversion of pyruvate to lactate.…”
Section: Introductionmentioning
confidence: 99%
“… 1 It is also possible for the reaction products in microdroplets to differ substantially compared to those from the same reaction conditions in bulk solution. 2 Recent work has demonstrated that aqueous microdroplets can cause spontaneous reduction. Two examples are the formation of gold nanoparticles and nanowires from aqueous microdroplets containing only chloroauric acid, 3 and the reduction of a number of different organic compounds dissolved in aqueous microdroplets, such as the conversion of pyruvate to lactate.…”
Section: Introductionmentioning
confidence: 99%
“…Microdroplet chemistry has emerged as a unique platform for studying and performing chemical reactions. [16][17][18][19][20][21][22] The ESI/ ESSI as the main setup to generate charged microdroplets is usually accompanied by special redox reactions, which have been used for some synthesis reaction and nanomaterials. 23,24 Microdroplets as microreactors combined with on-line MS have been used to capture and identify transient intermediates of organic reactions, and microdroplet chemistry has been broadly applied in the eld of bioanalytical detection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acceleration, microdroplet reactions also show better selectivity and reactivity than bulk-phase reactions. Gao and coworkers reported the highly selective synthesis of 2-phenyl-2,3-dihydrophthalazine-1,4-dione in microdroplets, which was attributed to the surface reactions in microdroplets at low pH values (Gao et al, 2019). Furthermore, Gnanamani et al (2020) found the chemoselective N-alkylation of indoles in aqueous microdroplets by catalysis-free ESSI, better than C-alkylation in bulk reactions with catalysts.…”
Section: Microdroplet Reactionsmentioning
confidence: 99%